Bluey : Shadowlands - BBC Studios; Penguin Young Readers Group (New York, 2024)
"Bluey, Coco, and Snickers are playing Shadowlands, but Coco keeps wanting to change the rules! Can the three friends reach the cupcakes without breaking the rules?"--
Keywords: Bluey; (Fictitious character); Juvenile fiction; Juvenile fiction; Cupcakes; Juvenile fiction; Play; Juvenile fiction; Shades and shadows; Juvenile fiction; Friendship; Juvenile fiction; Dogs; Juvenile fiction; Australian cattle dog; Animal fiction; Adaptations